2022
DOI: 10.1053/j.gastro.2021.09.055
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Response to Coronavirus Disease 2019 (COVID-19) Vaccination in Patients With Immune-Mediated Inflammatory Diseases: A Systematic Review and Meta-analysis

Abstract: Background and aims Patients with immune-mediated inflammatory diseases (IMIDs) have an increased risk of COVID-19, primarily attributed to the use of immunosuppressive drugs such as glucocorticoids, which may attenuate the response to vaccines. This meta-analysis aims to assess the serologic response to COVID-19 vaccination in patients with IMIDs. Methods Electronic databases were searched on August 1, 2021 for observational studies. Data including reference population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
39
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 45 publications
(50 reference statements)
7
39
2
1
Order By: Relevance
“…Therefore, the clinical effectiveness might remain sub-optimal compared to healthy population. The seroconversion after 2 doses was 40.1%, much lower than the rates reported in other vulnerable population, such as patients with immune-mediated inflammatory diseases (73.2%) [8] , cancer patients (51%) [9] , and patients with end-stage kidney disease (86%) [10] . Thus, SOTRs should receive the complete vaccination regimen without delay.…”
mentioning
confidence: 91%
“…Therefore, the clinical effectiveness might remain sub-optimal compared to healthy population. The seroconversion after 2 doses was 40.1%, much lower than the rates reported in other vulnerable population, such as patients with immune-mediated inflammatory diseases (73.2%) [8] , cancer patients (51%) [9] , and patients with end-stage kidney disease (86%) [10] . Thus, SOTRs should receive the complete vaccination regimen without delay.…”
mentioning
confidence: 91%
“…Although many IMID patients mount adequate serological responses to vaccination after two doses of an mRNA vaccine, a proportion of IMID patients show reduced responses compared to healthy controls, 7–13 as confirmed in recent meta-analyses. 14,15 In particular, patients receiving glucocorticoids, methotrexate, anti-TNF and B-cell depleting therapy may have attenuated serological responses to COVID-19 vaccines. 7,11,13,14,16 A small study of 23 IMID patients showed that patients on anti-TNF therapy have greater waning of humoral immunity compared to healthy controls, 13 as confirmed in a larger study still in preprint.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 In particular, patients receiving glucocorticoids, methotrexate, anti-TNF and B-cell depleting therapy may have attenuated serological responses to COVID-19 vaccines. 7,11,13,14,16 A small study of 23 IMID patients showed that patients on anti-TNF therapy have greater waning of humoral immunity compared to healthy controls, 13 as confirmed in a larger study still in preprint. 17…”
Section: Introductionmentioning
confidence: 99%
“…Drugs targeting tumor necrosis factor (TNF), such as infliximab, are the most frequently prescribed biological therapies used in the treatment of immune-mediated inflammatory disorders (IMIDs). Observational studies indicate that most patients with inflammatory bowel disease (IBD), an archetypal IMID, mount serological responses following SARS-CoV-2 vaccines, although most were underpowered to discern the impact of specific drugs, including immunomodulators (azathioprine, mercaptopurine, and methotrexate) and/or biologic therapies 58 . We reported that antibody responses following SARS-CoV-2 infection 9,10 or a single-dose of either the BNT162b2 or ChAdOx1 nCoV-19 SARS-CoV-2 vaccines were impaired in anti-TNF treated patients when compared to vedolizumab treated patients 11 .…”
Section: Introductionmentioning
confidence: 99%